Penguatan Pemahaman Siswa Kelas Xii Melalui Pelatihan Akuntansi - Eka Merdekawati; Ratih Pratiwi; Aulia Hidayati (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
SMA Negeri 6 Bogor is a senior high school in the city of Bogor. The majors at SMA Negeri 6 are science and social studies, one of the problems faced during online schools is regarding the understanding and ability of class XII students, especially social studies majors in accounting subjects, so there are concerns by the teacher that it will have an impact on students' final grades. The Accounting Study Program of college of Vocational Studies of IPB which consists of lecturers and students conducts accounting training for class XII students majoring in accounting with basic accounting materials and is proficient in preparing financial reports. This activity lasted for 1 day with 67 participants. The method applied in this community service activity is a descriptive analysis method with lectures and accounting practices from journal recording to the preparation of financial reports. The purpose of this community service activity is to strengthen understanding of accounting and proficient in preparing financial reports for students of SMAN 6 Bogor. Based on the post test results, it is known that 85% of students at SMAN 6 Bogor majoring in accounting are able to improve their understanding of accounting and prepare financial reports correctly, besides that students become motivated to study accounting and are optimistic that they will get good grades on the exam later.